2013
DOI: 10.3109/03009734.2013.801059
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care in COPD—web survey in Sweden highlights the current situation for a vulnerable group of patients

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is a common cause of death. Despite the heavy symptom burden in late stages, these patients are relatively seldom referred to specialist palliative care.MethodsA web-based survey concerning medical and organizational aspects of palliative care in COPD was distributed to respiratory physicians in Sweden. There were 93 respondents included in the study.ResultsPalliative care issues were regularly discussed with the patients according to a third of the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Since pulmonologists have a central role in providing good quality palliative care for patients with COPD, their view on this subject is important 17. There are already survey studies that explore their current working situation regarding palliative care for patients with COPD 18,19. This survey study, however, is the first to take the view and wishes of pulmonologists into account in order to guide future research and service development.…”
Section: Discussionmentioning
confidence: 99%
“…Since pulmonologists have a central role in providing good quality palliative care for patients with COPD, their view on this subject is important 17. There are already survey studies that explore their current working situation regarding palliative care for patients with COPD 18,19. This survey study, however, is the first to take the view and wishes of pulmonologists into account in order to guide future research and service development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified models of palliative care for patients with ILD and COPD, advocating the introduction of specialist palliative care early in a patient's disease trajectory (Higginson et al., ) or when a patients’ symptom management becomes too complex for generalists to manage (Strang, Ekberg‐Jansson, Strang, & Larsson, ). In the present study participants perceived that specialist palliative care services were not involved with the majority of patients, concurring with previous findings related to patients with ILD (Bajwah et al., ; Lindell et al., ) and COPD (Beernaert et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In stage IV, almost 20% of the patients suffer from a severely impaired HRQOL, and also in stage II, the corresponding proportion is around 8%. A palliative approach with four dimensions (physical, psychological, social, and spiritual) strives to see the person as a whole and it is known that, among other things, psychological and existential issues are common – and these are questions that palliative care has been used to dealing with ( 24 ). A possibility to alleviate the heavy symptom burden, especially in late stages, would be to cooperate with the palliative care service.…”
Section: Discussionmentioning
confidence: 99%